Money, interest rates and the real activity - Hao Hong (Cardiff University, Cardiff Business School, 2011)
This paper examines the effectiveness of monetary aggregates through various nominal interest rates by integrating the financial sector into the Cash-in-Advance (CIA) economy. The model assumes that there are two types of representative agents in the financial sector, which are: productive banks and financial intermediates. The productive banks supply a financial service, which is an exchange technology service to households and financial intermediates receive savings fund from savers and offer loans to borrowers. The monetary expansions are increased banking costs through the rate of inflation. It leads households to use more exchange credit relative to cash at the goods market. Since the number of savings funds is equal to the number of exchange credits used at the goods market, money injections are lower the nominal interest rate on saving as the saving fund increases with exchange credit. By assuming that firms are the only borrowers at the capital market from Fuerst (1992), a lower nominal interest rate on the saving fund reduces the marginal cost of labour and increases labour demand. Meanwhile, the increasing marginal cost of money through the expected inflation effect has a negative effect on labour supply. With labour demand dominating labour supply effects, both output and employment increase with monetary expansion. The paper is able to generate a decreasing nominal interest rate with an increasing money supply with an absence of limited participation monetary shocks from Lucas (1990); and by allowing firms to borrow wage bills payment from financial intermediates, it examines the positive response of aggregate output subject to monetary expansion under flexible price framework.
Keywords: E10; E44; E51; 330; monetary transmission; business cycles; banking sector; interest rates; Finanzmarkt; Finanzintermediär; Zinspolitik; Transmissionsmechanismus; Makroökonomischer Einfluss; Theorie